Why do we overestimate others' willingness to pay? - William J. Matthews; Ana I. Gheorghiu; Mitchell J. Callan (Judgment and Decision Making, 2016)
People typically overestimate how much others are prepared to pay for consumer goods and services. We investigated the extent to which latent beliefs about others’ affluence contribute to this overestimation. In Studies 1, 2a, and 2b we found that participants, on average, judge the other people taking part in the study to “have more money” and “have more disposable income” than themselves. The extent of these beliefs positively correlated with the overestimation of willingness to pay (WTP). Study 3 shows that the link between income-beliefs and WTP is causal, and Studies 4, 5a, and 5b show that it holds in a between-group design with a real financial transaction and is unaffected by accuracy incentives. Study 6 examines estimates of others’ income in more detail and, in conjunction with the earlier studies, indicates that participants’ reported beliefs about others’ affluence depend upon the framing of the question. Together, the data indicate that individual differences in the overestimation effect are partly due to differing affluence-beliefs, and that an overall affluence-estimation bias may contribute to the net tendency to overestimate other people’s willingness to pay.